(untitled) (AYUSHDHARA, 2019)
Introduction: Gandhak is one among the mineral drug explained in Uparasa Varga. It possesses Rasayana property. It attains therapeutic properties with proper Shodhana processes by Godugdha and by Bhringraj Swaras. Assessment of immunomodulatory effect of Bhringraj Swaras Shodhit Gandhak and Godugdha Shodhit Gandhak may provide evidence base for its textual reference and analysis of these Shodhit Gandhak contributes to establish standards for quality control. Method: Shuddha Gandhak by Godugdha and by Bhringraj Swaras prepared as per Rasaratnasamuchchaya and subjected to Immunomodulatory activity by Neutrophil Function Assay test with four parameters NBT test, phagocytosis, candidacidal assay and Neutrophils locomotion (chemotaxis) test. Results: In Immuno-modulatory assay different concentrations of Godugdha Shodhit Gandhaka and Bhringraj Swaras Shodhit Gandhaka shown significant increase in phagocytic activity, candidacidal capacity, locomotion and activation of Neutrophils for phagocytosis. Conclusion: Godugdha Shodhit Gandhaka and Bhringraj Swaras Shodhit Gandhaka shown significant immunomodulatory effect. Statistically there is no significant difference between Godugdha Shodhit Gandhaka and Bhringraj Swaras Shodhit Gandhaka.